Mora Castro, Albert (2020). Conocer para transformar. Métodos y técnicas de investigación en Trabajo Social. Valencia: Tirant Humanidades. 326 pp. ISBN: 978-84-18329-38-8 - Caravantes López de Lerma, Glòria María (Cuadernos de Trabajo Social, 2021)
Understanding the social reality and the phenomena studied by Social Work, as well as other related disciplines, requires a rigorous analysis based on the scientific method. In Knowing to transform. Research Methods and Techniques in Social Work, the author invites us to reflect and delve into the multiple possibilities that research offers to obtain answers to our research questions to transform reality in the exercise of our profession. The work begins with a prologue by the professor at the University of Valencia, María Eugenia González Sanjuán, where she encourages interested people with warm words to get involved in reading the book, highlighting the relevance of social research methods and techniques in the discipline of Social work. The book continues with the introductory part prepared by the author himself, Albert Mora Castro, who, through a personal account, reveals his professional career, highlighting that “studying Social Work was the most important professional decision of my life. With the help of several teachers, some of whom are my classmates today, I discovered professional Social Work, its scientific component and its important political mission and I understood that, without this discipline, without this profession, our society would be much more unfair, unequal and inhumane ”. In this way, a manual is presented for both students and professionals in Social Work written from Mora’s personal career and extensive professional and academic experience. The manual is organized around three thematic axes: a first part where the research in the field of Social Work and the logical sequence in the social research process is contextualized; a second part where the main techniques of the quantitative method are described; and the third part referring to the main qualitative techniques. These three blocks have been organized into a total of ten chapters combining theory with practical examples from the author’s professional career. The starting point of the work begins by delving into the roots of social research in the field of Social Work, underlining the indissoluble relationship between research and discipline as an essential aspect in the development of the professional practice of social workers. The second chapter illustrates the theory through practical examples on how to develop the research process, posing the different types of design and on how to approach them from participatory and biographical strategies, as well as the types of social research. This first block ends with the reference to the research carried out from the documentary and statistical sources, highlighting both the types of secondary sources, the content analysis, as well as the advantages and disadvantages of their use, among others. The second thematic block related to the quantitative method begins by dedicating an extensive chapter to measurement in the social sciences. In the case of measurement, the exposed content relative to the operationalization process is highly relevant, where the author argues the differences between concepts, dimensions, indicators and indices; key issues to differentiate at the beginning and definition of the research process. Likewise, the fourth chapter explains the different types of variables (according to the measurement scale, the level of abstraction, the function in the research and according to the measurement level), the attitudes measurement scales (Likert scale, scale of Bogardus social distances, Osgood’s semantic differential scale and scale of self-positioning intervals and ends with two questions to consider in the measurement process in social sciences: errors (systematic or constant and random, among others) and validity and Reliability. The manual continues exposing the survey technique in the fifth chapter, describing both its modalities, design, utilities and development phases. The sample design introduced in the sixth chapter presents the fundamental bases for the construction of the sampling frame, deepening the definition of the population under study, in its configuration and in the size of the sample. Likewise, the author dedicates good part from this chapter to the enunciation of the types of sampling, reflecting in each one of them both the differences and similarities and facilitating the reader’s selection of one or the other depending on the research they wish to carry out. Next, a brief description of the statistical analysis is introduced, highlighting three essential issues in this regard: the coding process and the design of the data matrix, the univariate analysis and the bivariate analysis. The third thematic block includes the last three chapters exposing throughout them the qualitative techniques related to observation, the in-depth interview and the discussion group. In the first case, participant observation is defined as a qualitative technique, the different existing modalities and their utilities. In addition, the author extensively explains how to develop this technique from its design to its registration and analysis in the development of an investigation. In relation to the qualitative technique par excellence, the in-depth interview, the author delves into his analysis from the point of view of its description, design, development and analysis of the information from it, with special mention to the process of transcription, coding of the information and final analysis. Lastly, the manual concludes with the exposition of the discussion group technique, deepening in the same way as the previous ones, in its description, its design and in the analysis of the information. With all this, knowing to transform, draws a range of possibilities to address social research from our profession and discipline: Social Work. The constant recurrence to practical research examples, product of the author’s professional career, facilitates both the reading and understanding of the theory, also accompanied by simple figures and diagrams to enter the field of research, as well as to develop studies and rigorous analysis. From the professional experience of Albert Mora, the manual highlights the relevance of research in Social Work, since only with scientific knowledge as a pillar, current and future generations of social workers will be able to face the present and future challenges of our profession.